Fruit Trees and Agro-Industry: Cans, Oil and Timber (Chile and Cuyo, 1550-1850) [Frutales y Agroindustria: Conservas, Aceites y Maderas (Chile y Cuyo, 1550-1850)] - Lacoste, P (2011)
The rapid propagation of European fruit-bearing plants in Chile and Cuyo led to the problem of their exploitation, which was a complex issue in the period before the availability of means of refrigeration. The response was to encourage agro-industrial activity. Some fruits were conserved through a process of dehydration and others were used in the making of oils. Some of these products were commercialised on the domestic market and others were exported, especially to Peru. There was also an improved use of the timber from fruit trees in both the construction industry and carpentry and cabinet-making. These activities ensured the economic viability of fruit-growing and made it possible for it to expand in the region under analysis.